Recycling petrochemical industry wastewater for constructed wetland development through phytoremediation technology / Sarifah Fauziah Syed Draman ... [et al.] - Syed Draman, Sarifah Fauziah; Mohd, Norzila; Salleh, Mohd Shahrul Nizam; Ahmad, Nurul ‘Uyun (2018)
Tasik Puteri is a recreational lake for few activities such as scuba diving, kayaking and swimming during the dry season. However, this lake was an iron ore mining site with the remaining contaminants and heavy metal of the lake can harm the people who directly get into contact with the lake water. The present study focused on investigating the phytoremediation potential of locally available perennial aquatic plants in the treatment process of water from Tasik Puteri, which was contaminated with mining effluent. The effluent was treated with water hyacinth (Eichhomia crassipes) and water lettuces (Salvinia molesta and Pistia stratiotes) in a constructed wetland for a period of 28 days. The effluent treatment efficiency was determined by measuring the effluent quality over the experimental period. Five water parameters such as the total iron (TI), total phosphorus (TP), chemical oxygen demand (COD), electrical conductivity (EC) and turbidity were examined using standard laboratory procedures. The results indicated that the three plants were able to remove the contaminants. After 28 days, the physical observation shows that the water hyacinth was healthier than the water lettuces. Considerable decrements in concentration were recorded in TI, TP and EC, but fluctuation in COD and turbidity value were observed. Comparison results by the plants indicated that after 28 days, water hyacinth was the most effective plant in removing phosporus, COD and EC of the mining lake with 97.3%, 70.5% and 22.2% removal, respectively. Furthermore, water lettuce (P. stratiotes) was the most effective plant in removing iron (96.0%) and the turbidity (50.0%) of the mining lake. S. molesta showed the lowest removal capability for all experimental parameters. In conclusion, water hyacinth and water lettuces had shown better capability in removing heavy metals and other contaminants with# crassipes has the highest survivability in the lake water.